A Comparative Study on the Pulsed UV and the Low‐Pressure UV Inactivation of a Range of Microbial Species in Water. (1st December 2014) - Garvey, Mary; Thokala, Nikhil; Rowan, Neil
ABSTRACT: : Research into alternative methods of disinfecting water and wastewater has proven necessary due to the emergence of chlorine‐resistant organisms and the disinfection byproducts associated with chlorine use. The use of UV light to inactivate microbial species has proven effective, however; standard UV lamps have proven to be less effective in their ability to inactivate parasites and bacterial endospores in water treatment settings. Pulsed UV (PUV) light may potentially provide a novel alternative to water and wastewater disinfection. Research outlined in this study assesses the potential of a novel PUV system for the rapid and reproducible inactivation of a range of test species including Bacillus endospores. In comparison to standard low‐pressure (LP) UV lamps, this PUV system provided significantly higher levels of inactivation for all test species. Furthermore, there was a remarkable decrease in time needed to obtain significant inactivation rates following treatment with PUV compared to LP‐UV. With the PUV system, a 70‐second treatment time (7.65 μJ/cm 2 ) resulted in similar inactivation rates of Bacillus endospores to that of the LP‐UV inactivation of their vegetative counterpart. Also, at PUV doses exceeding 4.32 J/cm 2, there was not a significant difference in the PUV inactivation of Bacillus endospores in the absence or presence of 10 ppm organic matter. However, the presence of organic matter resulted in a significant reduction in microbial inactivation for all treatment doses using the LP‐UV system. The findings of this study suggest that PUV technology may provide a rapid effective method for the disinfection of water and wastewater.